Canagliflozin-Induced Diabetic Ketoacidosis - Jessica Turner MSIV; Tahmina Begum MD; Roger D. Smalligan MD, MPH (Journal of Investigative Medicine High Impact Case Reports, 2016)
Introduction: Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are relatively new antihyperglycemic agents that lower renal glucose reabsorption. They are used as adjunctive therapy to standard diabetes treatment. Case Report: We present the case of a 62-year-old woman with a past medical history of type 2 diabetes mellitus and sudden-onset diabetic ketoacidosis (DKA). Use of canagliflozin, a SGLT-2 inhibitor, was determined to be the cause of the DKA. The patient ultimately recovered after 5 days in the intensive care unit. She was changed to long- and short-acting insulins and instructed to avoid canagliflozin. Conclusion: Although SGLT-2 inhibitors are effective at lowering a patient’s hemoglobin A1C, physicians must be aware of the rare but dangerous potential adverse effect of inducing DKA. This article reports an illustrative case and presents a review of the literature.